Increasing Income Through Financial Management And Entrepreneurial Innovation - Widia Asmaraningtyas, Lussy; Sriwidjaja, Sriwidjaja; Wajdi, Hamim; Asfali, Imam (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to examine increasing income through financial management and entrepreneurial innovation. This research is literature so that the form of research is descriptive qualitative. Literature study through books and related scientific journals. Performance is the result of various continuous management decisions to achieve certain goals effectively and efficiently in accordance with what is desired about the achievements or setbacks. Company performance is an achievement of goals by individuals and organizations effectively and efficiently. Effectiveness relates to its ability to achieve the desired goals, while efficiency describes how much input is needed to produce an output. Financial information helps to assess the company's ability to meet its obligations, increase capacity, and obtain funding, helping to assess the quality of future earnings and cash flows. Good financial management behavior will be able to manage business finances well. Innovation as creativity provides added value to the resources owned. Innovation is to take advantage of change rather than create it. The ability to innovate is needed in a business that has many competitors and is prone to saturation.